Delayed Neurological Deficits after Osteoporotic Vertebral Fractures: Clinical Outcomes after Surgery - Yip-Kan Yeung; Sheung-Tung Ho (Asian Spine Journal, 2017)
Study DesignRetrospective cohort.PurposeTo review the clinical presentation of operated patients with delayed neurological deficits after osteoporotic vertebral fractures (OVFs).Overview of LiteratureDelayed neurological deficits can occur from 1 week to 5.7 months after OVFs. Baba has reported 78% good-to-excellent improvement (i.e., ≥50%) after 20 posterior (Cotrel-Dubousset) and 7 anterior (Kaneda in 4, Zielke ventral derotational spondylodesis in 2, and un-instrumented anterior fusion in 1) fusions. Predictive factors for neurological deficits include burst type, vacuum sign, kyphosis, angular instability, and retropulsion.MethodsPatients with neurological deficits after OVF who received spinal operations between 2000 and 2016 were included.ResultsTotally, 28 patients with a mean age of 77 years underwent surgery. Neurological deficits occurred at an average of 5.4 weeks after the onset of back pain. The most common site was L1. Burst fracture was present in 14 patients and vacuum sign in seven. Surgery was performed within an average of 3.9 days of the onset of neurological deficit. Baba's score improved significantly from 5.96 to 9.81, with good-to-excellent improvement in 18 (64%) patients. Better outcomes based on Baba's scores (improvement>60% [median]) were associated with compression fractures, preoperative retropulsion of <41%, and correction of >16%. Poor improvement in Baba's scores (<25%) was associated with surgical complications and burst fracture type. Twenty-two patients (79%) regained walking ability, and seven of 15 (47%) patients demonstrated improved sphincter control at the latest follow-up. Six Frankel grade B patients did not achieve neurological recovery, four of whom exhibited postoperative surgical complications and died at 2 years because of medical problems. Implant migration occurred in six patients, albeit this was of no clinical significance.ConclusionsAlthough OVFs are commonly considered benign, delayed neurological deficits can occur. The significant improvement in clinical function after surgery for neurological deficits is associated with compression (and not burst) fractures, lack of surgical complications, and optimal restoration of retropulsion.